Review of the Literatures on Stock Price Behavior of Malaysia - Ruhani, Fatima; Islam, Md. Aminul; Ahmad, Tunku Salha Tunku (International Journal of Islamic Business & Management, 2018)
Stock price behavior is one of the core concerns of researchers and finance scholars from more than a half-century of years. Most of the times, they have tried to identify unexplored anomalies that could be used to explain stock price movement in the different stock market. As a result, we have found different models and theories relating to stock price behavior as well as the efficiency of the stock market. Malaysian stock market is considered the second among the largest South East Asian stock markets according to its domestic market capitalization. A considerable number of researches have already been done on the stock price behavior of Malaysian stock market. This study reviews the existing literatures on the stock price behavior of Malaysian stock markets within two wings, literatures on efficient market hypothesis of Malaysian market and the effect of economic and financial variables on the stock price.